2016
DOI: 10.1186/s12859-016-0970-4
|View full text |Cite
|
Sign up to set email alerts
|

MetICA: independent component analysis for high-resolution mass-spectrometry based non-targeted metabolomics

Abstract: BackgroundInterpreting non-targeted metabolomics data remains a challenging task. Signals from non-targeted metabolomics studies stem from a combination of biological causes, complex interactions between them and experimental bias/noise. The resulting data matrix usually contain huge number of variables and only few samples, and classical techniques using nonlinear mapping could result in computational complexity and overfitting. Independent Component Analysis (ICA) as a linear method could potentially bring m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…For complex biological processes such as those of the CNS or systemic aging, it behooves researchers to disentangle these processes into more manageable pieces; pieces emerging from the inherent structure of the data. Mutually independent "omic-modules" defined by their feature to input data relationships may prove essential for synthesizing a holistic description of biology (Liu et al, 2016). We struggled to define the role of some of our fly modules in part due to poor documentation of sample preparation procedures and the exact genotypes utilized; deficiencies that could have been attenuated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For complex biological processes such as those of the CNS or systemic aging, it behooves researchers to disentangle these processes into more manageable pieces; pieces emerging from the inherent structure of the data. Mutually independent "omic-modules" defined by their feature to input data relationships may prove essential for synthesizing a holistic description of biology (Liu et al, 2016). We struggled to define the role of some of our fly modules in part due to poor documentation of sample preparation procedures and the exact genotypes utilized; deficiencies that could have been attenuated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A new ICA approach called MetICA was applied to experimental mass spectrometry (MS)-based, non-targeted metabolomics data, which allowed to understand how non-targeted metabolomics data reflect biological nature and technical phenomena. The authors concluded that an optimal ICA model should be selected by optimizing the number of reliable components instead of just trying to fit the data [54].…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…It is clear that the range of applications of ICA to different types of chromatographic profiles should increase in the near future similarly to the alternative technique, MCR-ALS, which is widely used in chromatographic data analysis [45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Open digital repositories can be used to archive current-state full scan HRMS analysis for retrospective and joint exploitation [ 53 , 54 ]. At the same time, a bunch of bio-informatics tools including innovative clustering algorithms from metabolomics and genomics including independent component analysis (ICA) and cytoscape/ClueGO pathway analysis [ 55 , 56 ], hierarchical clustering, K -means, self-organizing maps and fuzzy clustering [ 57 , 58 ] are available and help unravel big and complex analytical datasets. It may be assumed that complex environmental mixtures in water bodies are not just randomly composed but the result of confluence of source-related patterns modified by environmental fate.…”
Section: Advanced Chemical Monitoring and Risk Assessmentmentioning
confidence: 99%